PENEGAKAN HUKUM PIDANA DALAM UPAYA PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG YANG BERASAL DARI HASIL TINDAK PIDANA NARKOTIKA DI KOTA PEKANBARU (Studi Pada Kejaksaan Negeri Pekanbaru) - Ananta, Bella; Effendi, Erdianto; , Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The crime of illicit drug trafficking has long been believed to have a close relationship with the money laundering process. Organized crime always uses this money laundering method to conceal, disguise or obscure the illicit business result in order to appear as if it were the result of legitimate activities. The proceeds of the narcotics sale are used again to commit a similar crime or develop new crimes. Background of illegal narcotics perpetrators who transfer and conceal the property of proceeds of crime through the financial system and reinvest the proceeds of crime for further criminal acts or into legitimate business.This type of research can be classified with the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This study was conducted in the jurisdiction of the Pekanbaru District Attorney, while the population and sample were the whole parties related to the problems studied in this study. Sources of data used, primary data and secondary data and tertiary data, data collection techniques in this study by observation, interview and literature study.From the results of this study that the authors do can be concluded. First, the process of the case has been implemented starting from the research process. Police investigator investigations, complete court files (P21), court proceedings to court, indictment, prosecution, verdict, until the prosecutor executes the judge's verdict. Secondly, the obstacles faced coming from Narcotics crime are divided into 2, namely Internal Barrier: Politic Will or the will of the authorities and still lack of training and money laundering education on a scale. External Barriers: The limited authority of PPATK, For Financial Service Providers / CHD has not been optimal with the principle of knowing the customer, understanding of reversing or reversing the burden of proof.Keywords: Law Enforcement - Proof - Money Laundering